Management Citizenship Education in Elementary Schools The forerunner of the Community in Facing the Challenges of Smart Cities - Bahdin Nur Tanjung (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
A study of citizenship education in elementary schools is a sensitive matter for us to discuss being a big topic, because in the view of the state is that every citizen must have intelligence both in terms of intellectual, spiritual, and emotional. The study in the view of civil society from several experts stated that, the concept of smart city must have a competency for its people to be able and accustomed to in any situation in this case the community (civil society) must apply the view of citizenship education that makes the embryo of the city become smart and superior. innovating every activity without reducing the values of legal and customary norms in the midst of the new ideas about the smart city, therefore smart cities should not be able to get out of the norm rules that exist in citizenship education especially at the elementary school level. The research method by the author uses the systematic method of Literature Review (SLR), by gathering several sources of information from journals, books and other articles. To improve the source of reading that will be produced by the reader later. Then after the sources are collected, the new author can conclude what results have been obtained from this reading source